User's perspective towards safety awareness on escalator accident at the Shopping Mall / Nur Syahira Mohd Shah and Syarifah Nur Nazihah Syed Jamalulil - Mohd Shah, Nur Syahira; Syed Jamalulil, Syarifah Nur Nazihah (2020)
Every day, there is no doubt that there are thousands and millions of people who use the escalator as transmission facilities in the world. Escalators could efficiently and safely be transporting people from floors to other floors in places such as shopping malls, cinemas, airports, railway stations, metro stations and other public places. Even though escalators seem safe to use, it can be extremely dangerous when used inappropriately or when not maintained correctly. This research was aimed to reduce escalator accidents among users at the shopping mall. The scope is focused on the user who used the escalator at Kuala Lumpur's shopping mall since there are few cases that have happened there. Three shopping malls were selected for this research. This research was conducted using quantitative methods and 82 questionnaires were distributed among the users. The data was then analysed using Statistical Package for Social Science (SPSS) version 26.0. The result shows that most of the respondents are aware of escalator accidents and have knowledge on escalator safety. In addition, the major factor that contributes to escalator accidents is the design factor. In order to reduce escalator accidents respondents suggested that the user have to follow safety guidelines and safety devices on escalators should be tested.